Analytical Analysis of Information-Centric Networking in Smart Grids - Ben Youssef, Nour El Houda (International journal of wireless information networks, 2022)
Smart grid (SG), the new generation of power system, is relying on its communication layer in order to fill the old electricity system gaps. The smart grid communication system (SGCS) has specific requirements to meet the expectations of providing a secure, reliable, and autonomic power system. A well-tailored communication layer is then imperative to guarantee efficient, reliable, and secure power supply. From our point of view, one of the most eligible candidates is the information-Centric paradigm whose principles suit well the smart grid communication needs. Indeed, due to the inherent fulfillment of the smart grid requirements, adopting information-Centric principles in smart grids is the subject of an ongoing research effort. However, the scale and the complexity of the smart grid communication layer hamper prototyping and validating research results especially when it comes to a new networking paradigm such as information-Centric networking (ICN). Thus, the main contribution of the present paper is to provide the research community with an analytical model that helps in first-round validations of research results in information -Centric smart grid communications. Smart grid network characteristics and information -Centric mechanisms were taken into account while realizing a mathematical model of information -Centric smart grid communications. It is, then, used to analytically highlight ICN benefits for the SGCS against the Internet protocol stack.